The between-person and within-person effects of intergroup contact on outgroup attitudes: a multi-context examination - Friehs, M-T; Bracegirdle, C; Reimer, NK; Woelfer, R; Schmidt, P; Wagner, U; Hewstone, M (SAGE Publications, 2023)
The extensive literature on the contact hypothesis reports a positive association between intergroup contact and outgroup attitudes, yet it remains unknown whether this association reflects within-person (i.e., situational changes within individuals) or between-person (i.e., stable differences between individuals) effects. To investigate this question, we applied (random-intercept) cross-lagged panel models in two studies featuring different samples, measurements, and contexts. We found longitudinal contact–attitude associations in cross-lagged panel models, which cannot differentiate within-person and between-person effects. In random-intercept cross-lagged panel models, we identified between-person effects but not within-person effects. These results conflict with the contact hypothesis, which assumes that contact leads to intra-individual attitude change. We further investigated whether between-person effects represent spurious correlations caused by potential confounders (demographic characteristics, personality, and intergroup ideologies), but found that this was not the case. Our findings highlight the need to further investigate within-person effects and potential explanations of between-person differences in contact and attitudes.